Estudio comparativo de los servidores hp, dell y lenovo para determinar cuál aportaría mayores beneficios. - Naranjo Gáleas, Karla Isabel (2023)
The present investigation consists of carrying out a comparative analysis of server brands such as: HP, Dell and Lenovo to determine which of them would provide greater benefits to companies. The purpose of this case study is to collect and provide appropriate information to those in charge of the systems department. Brands, models, features and also the price of each of the servers were investigated. A model for each brand was selected for the analysis, and the benefits offered by each of the servers were also described. This information was collected through different techniques such as documentary research, interviews and surveys that were carried out with teachers, technicians and students of the Faculty of Administration, Finance and Information Technology. According to the results obtained according to different criteria, techniques used and taking into account the cost of the servers, it resulted that the best option is the HP brand with the HPE ProLiant DL385 Gen11 model since this company offers the best quality in its products. In addition, the cost is accessible and optimal to be implemented in the customer service department of SMEs. According to the criteria of professionals and companies, they believe that for medium and large companies Lenovo would be ideal since they are suitable for office workloads and Dell for its level of technical support.